The 1997 Peace Accord and the Re-Emergence of Militancy in the Chittagong Hill Tracts: A Multidimensional Approach - Sadik, Muhammad Irfan (Academia Journal of Humanities & Social Sciences, 2025)
The peace accord between the Government of Bangladesh, and the Parbatya Chattogram Jana Sanghati Samiti (PCJSS) was signed on 2 December 1997, after a decade-long insurgency in the Chittagong hill tracts areas. These conflicts go back to the inception of the independent Bangladesh; as the majority of the population is Bengali, and therefore the other ethnic communities and tribes have always felt threatened by Bengali majorities, the government, its forces, and their policies upon them. Despite signing of the peace accord, the conflict between different ethnic communities and the security forces hasn’t made any progress of a total de-escalation of armed insurgency even after 27 years, as the peace treaty was signed by a few major ethnic communities, i.e. the Chakma, Marma, and Tripura and the Government of Bangladesh. It eventually made other small tribes marginalized in different aspects of life, and often resulted in direct armed conflicts. There are several questions and counter-questions to address this issue: How this hilly mountainous region became so prone to conflicts for fifty long years, why there are so many ethnic group fragmentations and what's their motive? Why does fighting break out so frequently with ethnic groups and security forces? How does reformation and implementing of peace accord can actually improve the scenario? How the Government of Bangladesh can achieve national integration along with national security? This paper addresses these questions with the brief description of ethnic diversity of different cultures, historical backgrounds of Chittagong Hill Tracts, critically evaluates the problems and drawbacks of 1997 peace accord along with implementation, and the hostile ethnopolitics, ethnic group fragmentation for political representation, military presence and dominance in the Chittagong Hill Tracts. It also proposes a multidimensional approach to resolve this fifty years long multifaceted crisis, encouraging a national integration.